EFFICIENCY USE LOW PRESURRE DRIP IRRIGATIONOF IN SMALL GARDENS - Murodov Otabek Ulugbekovich; Hojiyev Farrux O‘tkirovich; Ravshanov Umidjon Khalil o‘g‘li (TADQIQOTLAR, 2025)
The article discusses the technology of low pressure drip irrigation used in the irrigation of intensive gardens in the Republic. At the same time, the advantages and disadvantages of using irrigation in agriculture are analyzed and reported on the economics of water consumption in drip irrigation up to 20-60%, mineral fertilizers up to 50% and fuel lubricants up to 30%.